Vous êtes sur la page 1sur 2

# Notes on Linearization

Javier A. Kypuros, Ph.D. Assistant Professor University of Texas - Pan American Mechanical Engineering Department October 31, 2001
The following is an abbreviated discussion of the generalized linearization of a system of nonlinear, rst-order equations using the Taylor series expansion and the Jacobian matrix. Imagine a system of rst-order, nonlinear equations: x1 = f1 (x1 , x2 , . . . , xn , u1 , u2 , . . . , um ) x2 = f2 (x1 , x2 , . . . , xn , u1 , u2 , . . . , um ) . . . x3 = f3 (x1 , x2 , . . . , xn , u1 , u2 , . . . , um ) The general vector representation is x = f(x, u) where x1 u1 x2 u2 x = . and u = . . . . . . xn The generalized vector Taylor series expansion is f(x, u) = f(x0 , u0 ) +
where the Jacobian matrices are
f
1

(1)

un

## f(x0 , u0 ) f(x0 , u0 ) (x x0 ) + (u u0 ) + h.o.t. x u

f1 x2 f2 x2 . . . fn x2
1

(2)

x1 f f(x0 , u0 ) 2 = x1 . x . . fn x1

.. .

f1 xn f2 xn . . . fn xn x=x0 , u=u0

and

## f1 u1 u2 f f2 f(x0 , u0 ) 2 = u1 u2 . u . .. . . . . . fn fn u1 u2 If the point (x0 , u0 ) is an equilibrium, then by denition,

1

f1 un f2 . xn . . . fn un x=x0 , u=u0

f(x0 , u0 ) = 0. Take for example the following nonlinear, second-order equation + (1 + 2 ) + sin = F If we let x1 = , x2 = , and u = F, then we can rewrite this as a system of rst-order equations as x= x1 = x2 f1 (x1 , x1 , u) x2 = . 2 f2 (x2 , x2 , u) u (1 + x1 )x2 sin x1 1 2 1 x1 f(x, u) 0 = . 1 u

The Jacobian matrices for this system are f(x, u) 0 = 2x1 x2 cos x1 x and

These matrices must be evaluated at a point of equilibrium (x0 , u0 ). This means that f(x0 , u0 ) = so that we get x20 = 0 and sin x10 = u0 . Evaluating the Jacobian matrices at equilibrium gives us f(x0 , u0 ) 0 = cos x10 x x1 0 = x2 cos x10 1 1 x1 2 0 and f(x0 , u0 ) 0 = . 1 u u0 (1 + x2 x20 0 = 0 10 )x20 sin x10

## Substituting these results into Equation 1 results in x= 1 (1 + x1 2 ) 0 x1 x10 0 + (u u0 ). x2 x20 1

The following substitutions can be made x1 = x10 + x1 x1 = x1 x2 = x20 + x2 x2 = x2 u = u0 + u u = u giving us the nal result x= 0 x1 = x2 cos x10 1 (1 + x1 2 ) 0 0 x1 + u . x2 1